(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Pandit Madan Mohan Malviya, a prominent figure in India's freedom struggle, played a pivotal role in shaping modern Indian education. His efforts to fuse traditional Indian knowledge systems with modern Western education created a holistic framework that continues to influence Indian educational policies today.His contributions reflect a deep commitment to integrating traditional Indian knowledge with modern, Western education.His efforts to fuse traditional Indian knowledge systems with modern Western education created a holistic framework that continues to influence Indian educational policies today. Malviya's most significant achievement in education was the establishment of Banaras Hindu University (BHU) in 1916, a major educational institution that continues to stand as a pillar of higher education in India. This paper explores Malviya’s vision for education, his reforms, his advocacy for vernacular education, and the ways in which his contributions continue to influence the Indian education system. Keywords Pandit Madan Mohan Malviya, Banaras Hindu University, Indian Education, Nationalism, Educational Reforms